Faktor Terkait Kinerja Perawat di Rumah Sakit Datu Beru Takengon Tahun 2023 - Rana, Revaranda Genta; Nababan, Donal; Tarigan, Frida Lina; Sitorus, Mido Ester J; Wandra, Toni (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2024)
This research focuses on finding out factors related to the performance of nurses at Datu Beru Takengon Regional Hospital. The aim of this research is to determine the factors related to the performance of nurses at Datu Beru Regional Hospital. This research is a type of quantitative research, with a research design using a cross-sectional approach. The sample in this study consisted of 72 nurses at Datu Beru Takengon Regional Hospital using a simple random sampling technique, processing bivariate data using the chi-square test. The data collection method uses a questionnaire. The results of statistical tests show that there is no relationship between income and nurse performance (p value 0.399), there is no relationship between motivation and nurse performance (p value 0.605), there is a relationship between work stress and nurse performance (p value 0.000), and there is a relationship between workload and work behavior can be seen that (p value 0.000). Based on the assessment of the workload of room nurses, the results showed that the workload level of nurses at Datu Beru Regional Hospital was mostly moderate. The results obtained from the assessment of nurses' work stress were that the level of work stress for nurses at Datu Beru Regional Hospital was classified as moderate. There needs to be an evaluation of load, work stress and other possible factors so that the work tasks assigned to nurses are appropriate